Giving Children a Better Start : Preschool Attendance and School-Age Profiles - Berlinski, Samuel; Galiani, Sebastian; Manacorda, Marco (World Bank, Washington, DC, 2012)
The authors study the effect of pre-primary education on children's subsequent school outcomes by exploiting a unique feature of the Uruguayan household survey (ECH) that collects retrospective information on preschool attendance in the context of a rapid expansion in the supply of pre-primary places. Using a within household estimator, they find small gains from preschool attendance at early ages that magnify as children grow up. By age 15, treated children have accumulated 0.8 extra years of education and are 27 percentage points more likely to be in school compared with their untreated siblings. Instrumental variables estimates that control for nonrandom selection of siblings into preschool lead to similar results. The authors speculate that early grade repetition harms subsequent school progression and that pre-primary education appears as a successful policy option to prevent early grade failure and its long lasting consequences.